A new model for packing of type-I collagen molecules in the native fibril. Issue 10 (October 1981) - Piez, Karl A.; Trus, Benes L.
Abstract : A specific fibril model is presented consisting of bundles of five-stranded microfibrils, which are usually disordered (except axially) but under lateral compression become ordered. The features are as follows (where D = 234 residues or 67 nm): (1) D -staggered collagen molecules 4.5 D long in the helical microfibril have a left-handed supercoil with a pitch of 400–700 residues, but microfibrils need not have helical symmetry. (2) Straight-tilted 0.5- D overlap regions on a near-hexagonal lattice contribute the discrete x-ray diffraction reflections arising from lateral order, while the gap regions remain disordered. (3) The overlap regions are equivalent, but are crystallographically distinguished by systematic displacements from the near-hexagonal lattice. (4) The unit cell is the same as in a recently proposed three-dimensional crystal model, and calculated intensities in the equatorial region of the x-ray diffraction pattern agree with observed values.